THE EFFECT OF HIBISCUS SABDARIFFA LINN.ETHANOLIC EXTRACT ADMINISTRATION ON RAGE, GLP-1 AND GLP-1R EXPRESSIONIN HEART TISSUE OF DIABETIC MICE - Lestari YD; Santoso DIS; Goenarjo RA; Paramita N, (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Diabetes mellitus (DM) is a multifactorial disease associated with hyperglycemia and an increased risk of complications in the cardiovascular system. During hyperglycemia, there is a significant decrease in GLP-1 and GLP- 1R expression, which have been known to have protective effects on the cardiovascular system. Increased RAGE expression due to hyperglycemia can also lead to inflammation, contributing to the pathogenesis of diabetes complications, specifically cardiovascular diseases. Administration of Hibiscus sabdariffa Linn. (HSL) can improve cardiovascular function, partly by increasing GLP-1 expression and suppressing RAGE expression. The aim of this study is to investigate the effect of HSL administration on RAGE, GLP-1, and GLP-1R expression in the heart. This study is an experimental study using 9-to-11-week-old DDY mice divided into four groups: control (K), DM control (KDM), positive control DM with quercetin (KQ), and DM with HSL at a dose of 400 mg/kgBW (DM-HSL). The experimental animals received treatment for four weeks.The analysis of GLP-1R and RAGE expression was conducted using RT-PCR, while GLP-1 expression were obtained using the ELISA method. The results of this study indicate a decrease in RAGE expression and an increase in GLP-1 and GLP-1R expression in the hearts of diabetic mice. Quercetin administration was also found to decrease RAGE expression, increase GLP-1 expression, and raise GLP- 1R expression in the hearts of diabetic mice. These findings suggest that HSL administration has the potential to protect the cardiovascular system in diabetes, which is related to the activity of GLP-1 and GLP-1R and RAGE.